DFT Studies on Optimized Geometries for Thiazole Derivatives - Salimi, Farshid; Sahebalzamani, Hajar; Hezhabri, Elaheh; Minaei, Bita; Hajhosseini, Masoumeh (Asian Journal of Chemistry, 2012)
The molecular geometry and energies of N,N'-bis-(2-thiazol-yl)methylenediamine (1) in the ground state are calculated by using the density functional (HCTH/PBE1PBE) methods with 6-31G* basis sets. The calculated HOMO and LUMO energies also confirm that charge transfer occurs within the molecule. The geometries and energies obtained from HCTH/PBE1PBE/6-31G* calculations are in good agreement with the experimental data.